2020
DOI: 10.1186/s12885-020-06939-6
|View full text |Cite
|
Sign up to set email alerts
|

PPFIA1 expression associates with poor response to endocrine treatment in luminal breast cancer

Abstract: Background: PPFIA1 is an important regulator of cell migration and invasion, regulating focal adhesion signalling and disassembly. PPFIA1 is frequently amplified in breast cancer, and recent functional studies indicate that PPFIA1 is an important promoter of migration and invasion in breast cancer. This study aims to evaluate the utility of PPFIA1 expression in the luminal breast cancer as a prognostic marker to predict the response to endocrine therapy. Methods: Large, well-characterised cohorts of primary lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…explored the prognostic value of PPFIA1 alone or in combination with TMEM16A and FADD in patients with invasive ductal breast carcinoma, and they found that the combined expression was signi cantly associated with perineural invasion and a low disease-free survival rate. A recent study showed that the expression of PPFIA1 is closely related to poor response to endocrine treatment in luminal breast cancer [22]. Since PPFIA1 was found to be involved in the development of ESCC, we believe that PPFIA1 is likely to have a great impact on the survival of patients with ESCC.…”
Section: Discussionmentioning
confidence: 81%
“…explored the prognostic value of PPFIA1 alone or in combination with TMEM16A and FADD in patients with invasive ductal breast carcinoma, and they found that the combined expression was signi cantly associated with perineural invasion and a low disease-free survival rate. A recent study showed that the expression of PPFIA1 is closely related to poor response to endocrine treatment in luminal breast cancer [22]. Since PPFIA1 was found to be involved in the development of ESCC, we believe that PPFIA1 is likely to have a great impact on the survival of patients with ESCC.…”
Section: Discussionmentioning
confidence: 81%
“…To clarify the functions of DEGs, we further performed functional enrichment analysis. The proteins translated by DEGs were mainly located in extracellular regions and these genes were primarily implicated in tumor-related biological processes such as cell adhesion, wound healing, and extracellular matrix organization (Yu et al, 2019;Alfarsi et al, 2020;Liao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To better clarify the functions of DEGs, we further performed functional enrichment analysis. The proteins translated by DEGs were mainly located in extracellular regions and these genes were primarily implicated in tumor-related biological processes such as cell adhesion, wound healing and extracellular matrix organization [16][17][18].…”
Section: Discussionmentioning
confidence: 99%